Toxic Effects of Leaf and Flower Crude Extracts from Lantana camara on Tetranychus urticae - Srimongkolchai, W.; Vichitbandha , P.; Pung, T. (Asian Journal of Chemistry, 2013)
Leaves and flowers of L. camara were extracted by soxhlet separation for 8 h by n-hexane, dichloromethane and methanol, evaporated to dryness and kept at 4 ºC until toxicity tests. Twenty adult gravid females of T. urticae were placed on a mulberry leaf disc. Each type of plant extracts (1 % w/v) was applied on the leaf disc by 2 ways: no choice and choice bioassay. Results from no choice bioassay showed that the crude flower extracts had no toxicity. However, both dichloromethane and n-hexane extracts of L. camara's flowers repelled 66.04 ± 5.45 % and 60.83 ± 3.45 % T. urticae from the leaf discs. The dichloromethane, n-hexane and methanol extracts from L. camara's flowers reduced the oviposition per day rate of T. urticae to 42.3, 34.7 and 17.4 % when compare to ethanol-treated controls. The repellent effects of n-hexane and dichloromethane were observed with EC50's of 0.756 % and 0.902 %, respectively. Results from choice bioassay showed that the 1 % w/v of n-hexane and dichloromethane crude flower extracts repelled T. urticae to the untreated side at 72 h. The numbers of mites and their eggs on treated side were lower than on the untreated side.